Measurement and calculation of gas compressibility factor for condensate gas and natural gas under pressure up to 116MPa - Yan, Ke-Le; Liu, Huang; Sun, Chang-Yu; Ma, Qing-Lan; Chen, Guang-Jin; Shen, De-Ji; Xiao, Xiang-Jiao; Wang, Hai-Ying (The Journal of chemical thermodynamics, 2013)
•Volumetric properties of two reservoir fluid samples were measured with pressure up to 116MPa.•Dew point pressures at four temperatures for condensate gas sample are obtained.•Correlations and thermodynamic model for describing gas compressibility factor under high pressure were compared.•The thermodynamic model recommended is most suitable for fluids produced from reservoirs with a wide pressure range. The volumetric properties of two reservoir fluid samples collected from one condensate gas well and one natural gas well were measured under four groups of temperatures, respectively, with pressure up to 116MPa. For the two samples examined, the experimental results show that the gas compressibility factor increases with the increase of pressure. But the influence of the temperature is related to the range of the experimental pressure. It approximately decreases with the increase of temperature when the pressure is larger than (45 to 50)MPa, while there is the opposite trend when the pressure is lower than (45 to 50)MPa. The dew point pressure was also determined for the condensate gas sample, which decreases with the increase of temperature. The capabilities of four empirical correlations and a thermodynamic model based on equation of state for describing gas compressibility factor of reservoir fluids under high pressure were investigated. The comparison results show that the thermodynamic model recommended is the most suitable for fluids whatever produced from high-pressure reservoirs or conventional mild-pressure reservoirs.